Core collection construction and genetic diversity analysis of tea plant (Camellia sinensis [L:] O. Kuntze) accessions in Huangshan city using SSR markers - Xu Ruan; Qiong Wu; Xiaoyu Jiao; Dandan Liu; Minghui Sun; Leigang Wang; Wenjie Wang (PLoS ONE, 2025)
Assessing genetic diversity and building a core collection is essential to advancing tea plant breeding. In this study, ten SSR markers exhibiting robust amplification and polymorphism were employed to genotype 292 tea accessions sourced from various regions in Huangshan city. The results revealed significant genetic variation, encompassing 180 alleles. Genetic structure was evaluated using neighbor-joining clustering, principal coordinate analysis, and Structure analyses, which categorized the tea accessions into two primary clusters. The genetic diversity within these clusters demonstrated high similarity, likely due to their close geographical proximity. A core collection was established utilizing Core Hunter software, resulting in the selection of 35% of the accessions to effectively represent the genetic diversity of the entire collection. This core collection comprises 102 tea accessions, preserving a high percentage of allele richness and genetic diversity. This research offers valuable insights into genomics research and the sustainable management of tea plant genetic resources in Huangshan city.